2015
DOI: 10.3103/s0096392514030031
|View full text |Cite
|
Sign up to set email alerts
|

Influence of high-intensity sound vibration on rat behavior

Abstract: The influence of high intensity (110 dB) sound vibrations on experimental rats was studied on the behavior level. Classical behavioral tests (open field, hole board, light-dark box) were used to examine behavioral changes during 5 min acoustic impact of either audible or infrasound spectrum. Statistically sig nificant changes in locomotor activity and grooming reactions were observed, following either aural or infra sound impact. The set of observed effects could be classified as active avoidance reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
2
1
0
Order By: Relevance
“…These data suggest that noise stress affects the locomotor activity. Our data is in agreement with other studies in which noise at levels above 100 dB decreases locomotor activity in OF test [9,22]. Berezhnoy et al [22] exposed rats to the acute noise stress at 110 dB, and results showed a significant reduction of locomotor activity.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…These data suggest that noise stress affects the locomotor activity. Our data is in agreement with other studies in which noise at levels above 100 dB decreases locomotor activity in OF test [9,22]. Berezhnoy et al [22] exposed rats to the acute noise stress at 110 dB, and results showed a significant reduction of locomotor activity.…”
Section: Discussionsupporting
confidence: 83%
“…Our data is in agreement with other studies in which noise at levels above 100 dB decreases locomotor activity in OF test [9,22]. Berezhnoy et al [22] exposed rats to the acute noise stress at 110 dB, and results showed a significant reduction of locomotor activity. A study by Naqvi et al [9] also revealed an impact of sub-chronic noise stress at 100 dB on the decrease in the animals' locomotor activity.…”
Section: Discussionsupporting
confidence: 83%
“…In the range of IFS, comparative studies have shown that the auditory sensitivity of different species can vary widely. For instance, rats have poorer infrasonic hearing than humans, considering different sound pressure levels [5], but high-intensity (110 dB) IFS vibrations on experimental rats can be perceived, as they elicit active avoidance reactions [6]. Beside its auditory health effects, noise can cause nonauditory effects-such as annoyance, sleep disturbance, and psychological stress-that experimental and epidemiological evidence links to cardiovascular disease, including ischemic heart disease, heart failure, arterial hypertension, arrhythmia, and stroke [7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%